2010
DOI: 10.2147/opth.s11005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clear lens extraction and collamer lens implantation in high myopia

Abstract: Aim:To compare the outcomes of clear lens extraction and collamer lens implantation in high myopia. Patients and methods: Myopic patients younger than 40 years old with more than 12 diopters of myopia or who were not fit for laser-assisted in situ keratomileusis were included. Group 1 comprised patients undergoing clear lens extraction and Group 2 patients received the Visian implantable collamer lens. Outcome and complications were evaluated. Results: Postoperative best corrected visual acuity was -0.61 ± 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Jean Arne compared phakic intraocular lens (IOL) implantation with clear lens extraction (CLE) in 39 patients aged 30-50 years old and found a lower risk for loss of best correct visual acuity (BCVA) in the phakic IOL group at the one-year follow up [78]. In another study comparing refractive lens exchange (RLE) and Collamer lens (Visian) implantation in patients with myopia younger than 45 years old, the results revealed better outcomes in patients who underwent RLE [79]. In this study, patients in the RLE group experienced no serious complications, while those with the Visian implantation demonstrated pigment dispersion, lens opacity, macular hemorrhage, or pupillary block glaucoma [79].…”
Section: Refractive Lensectomy In Myopiamentioning
confidence: 99%
See 2 more Smart Citations
“…Jean Arne compared phakic intraocular lens (IOL) implantation with clear lens extraction (CLE) in 39 patients aged 30-50 years old and found a lower risk for loss of best correct visual acuity (BCVA) in the phakic IOL group at the one-year follow up [78]. In another study comparing refractive lens exchange (RLE) and Collamer lens (Visian) implantation in patients with myopia younger than 45 years old, the results revealed better outcomes in patients who underwent RLE [79]. In this study, patients in the RLE group experienced no serious complications, while those with the Visian implantation demonstrated pigment dispersion, lens opacity, macular hemorrhage, or pupillary block glaucoma [79].…”
Section: Refractive Lensectomy In Myopiamentioning
confidence: 99%
“…In another study comparing refractive lens exchange (RLE) and Collamer lens (Visian) implantation in patients with myopia younger than 45 years old, the results revealed better outcomes in patients who underwent RLE [79]. In this study, patients in the RLE group experienced no serious complications, while those with the Visian implantation demonstrated pigment dispersion, lens opacity, macular hemorrhage, or pupillary block glaucoma [79]. Additional studies examining the efficacy of RLE have demonstrated encouraging results and revealed a rapid and predictable improvement in vision in patients with high myopia as demonstrated by improved corrected distance visual acuity [77,[80][81][82].…”
Section: Refractive Lensectomy In Myopiamentioning
confidence: 99%
See 1 more Smart Citation
“…ICL (implantable collamer lens) implantation provides excellent visual quality in patients with high myopia and thin corneas [1][2][3]. But as an endophthalmologic procedure, the surgeon's learning curve remains a risk factor for some complications [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the widespread diffusion of phacoemulsification machines and phaco-trained surgeons have caused the minimum age for RLE to lower. [1][2][3][4][5][6][7][8][9][10] The increased popularity of RLE, 11,12 as for any medical advancement, forces us to redefine our ethical boundaries. The advantages of exchanging a normal, healthy lens for refractive purposes are counterbalanced by specific complications.…”
mentioning
confidence: 99%